Creating Students with Superior Character: Implementation of P5 Project in Mobilizing Schools - Fahri, Ardian; Yuliantri, Rhoma Dwi Aria; Khoiriyah, Febriana; Triansyah, Fadli Agus (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study aims to show and describe the implementation of the Pancasila Student Profile Strengthening Project (P5) at Bina Mulya High School, one of the pioneers of mobilizing schools in Pringsewu Regency, Lampung Province. The implementation of the project is crucial because there have been many incidents of violence, discrimination, and disrespect between religious communities in Indonesia due to a lack of understanding of the values of Pancasila as the basis of national unity and unity to realize the strengthening of the profile of Pancasila students and prepare a superior generation in the 21st century. The research method used is Descriptive Qualitative with data collection techniques through observation, interviews, and documentation. The results showed that the P5 Pancasila student profile strengthening project positively impacted students' understanding of Pancasila values and students' activeness in applying these values in daily life. The themes used by Bina Mulya High School are Voice of Democracy (24 Activities), Entrepreneurship (17 Activities), and Building His Spirit to Build His Body (19 Activities) which are carried out in 5 stages of the activity flow, namely Introduction, Contextualization, Action, Reflection, and Follow-up.